2018
DOI: 10.1525/mp.2018.35.3.253
|View full text |Cite
|
Sign up to set email alerts
|

Activity Analysis and Coordination in Continuous Responses to Music

Abstract: Music affects us physically and emotionally. Determining when changes in these reactions tend to manifest themselves can help us understand how and why. Activity Analysis quantifies alignment of response events across listeners and listenings through continuous responses to musical works. Its coordination tests allow us to determine if there is enough inter-response coherence to merit linking their summary time series to the musical event structure and to identify moments of exceptional alignment in response e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
4
12
0
Order By: Relevance
“…The authors found higher interrater reliability in the live concert setting than the other contexts, suggesting higher emotional convergence when viewing a live concert. A similar finding has been identified for continuous ratings of live music: in certain musical settings, continuous ratings were found to show a higher agreement among viewers of live vs. recorded concerts ( Upham and Mcadams, 2018 ). More recently, research has indicated that listeners display more vigorous head movements during a live concert than while listening to a recorded version of the same concert ( Swarbrick et al, 2019 ).…”
Section: Introductionsupporting
confidence: 76%
“…The authors found higher interrater reliability in the live concert setting than the other contexts, suggesting higher emotional convergence when viewing a live concert. A similar finding has been identified for continuous ratings of live music: in certain musical settings, continuous ratings were found to show a higher agreement among viewers of live vs. recorded concerts ( Upham and Mcadams, 2018 ). More recently, research has indicated that listeners display more vigorous head movements during a live concert than while listening to a recorded version of the same concert ( Swarbrick et al, 2019 ).…”
Section: Introductionsupporting
confidence: 76%
“…Another limitation of the regression study is related to the use of mean ratings of emotional intensity, which cannot account for response variability across participants. Activity analysis (Upham & McAdams, 2015) could be used in future to accompany this study to assess response coordination within and across the musician and nonmusician groups, as well as to pinpoint statistically significant moments of local activity for increasing or decreasing emotional intensity. This type of analysis would assist in disentangling instances where participants’ responses are coordinated and where they diverge, and whether these instances relate to particular moments within the shaping of orchestral gestures as shown on the visualizations.…”
Section: Discussionmentioning
confidence: 99%
“…For the main continuous ratings analysis, we first considered calculating an aggregated response series for each stimulus-the mean synchrony rating across all participants-to be predicted using the audio and visual features. However, continuous rating data for responses to music is often highly idiosyncratic (see for instance Dean, Bailes, & Dunsmuir, 2014, where inter-individual differences were greater within than between groups of different musical expertise levels), and the mean rating necessarily covers a smaller range of the response scale than the range employed by individual responses (Upham & McAdams, 2018). In addition, the average standard deviation between ratings across all timepoints in our dataset was 0.50 (25% of the range of the rating scale), which indicated a consistently large amount of variation between participants.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the average standard deviation between ratings across all timepoints in our dataset was 0.50 (25% of the range of the rating scale), which indicated a consistently large amount of variation between participants. We also considered employing a method based on identifying significant moments of coordination of responses between participants such as Activity Analysis (Upham & McAdams, 2018). However, the stimuli we employed were all shorter than the recommend two-minute duration for applying Activity Analysis, and hence would have required modification of the thresholds in a relatively arbitrary fashion to obtain promising results.…”
Section: Methodsmentioning
confidence: 99%